2020
DOI: 10.1016/j.molcel.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

PRIMPOL-Mediated Adaptive Response Suppresses Replication Fork Reversal in BRCA-Deficient Cells

Abstract: Summary Acute treatment with replication-stalling chemotherapeutics causes reversal of replication forks. BRCA proteins protect reversed forks from nucleolytic degradation, and their loss leads to chemosensitivity. Here, we show that fork degradation is no longer detectable in BRCA1-deficient cancer cells exposed to multiple cisplatin doses, mimicking a clinical treatment regimen. This effect depends on increased expression and chromatin loading of PRIMPOL and is regulated by ATR activity. Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
252
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(271 citation statements)
references
References 89 publications
(173 reference statements)
18
252
1
Order By: Relevance
“…We further speculate that E2F transcription is also induced in tumors undergoing repeated cycles of chemotherapy, and that increases in the E2F-dependent transcriptional program represent a potential source of resistance to anticancer drugs. In agreement with this idea, a recent study showed that a pre-exposure to cisplatin is sufficient to induce an ATRdependent adaptive response to subsequent cisplatin treatments that involves transcription of the PRIMPOL protein to rescue fork degradation in brca1 cancer cells 71 . This finding is in line with our model positioning ATR as a sensor of intrinsic or drug-induced replication stress and a regulator of genome stability through the modulation of the E2F transcription program and HR-coupled repair.…”
Section: Long-term Atr Inhibition Bypasses Overexpression Of E2f1mentioning
confidence: 69%
See 1 more Smart Citation
“…We further speculate that E2F transcription is also induced in tumors undergoing repeated cycles of chemotherapy, and that increases in the E2F-dependent transcriptional program represent a potential source of resistance to anticancer drugs. In agreement with this idea, a recent study showed that a pre-exposure to cisplatin is sufficient to induce an ATRdependent adaptive response to subsequent cisplatin treatments that involves transcription of the PRIMPOL protein to rescue fork degradation in brca1 cancer cells 71 . This finding is in line with our model positioning ATR as a sensor of intrinsic or drug-induced replication stress and a regulator of genome stability through the modulation of the E2F transcription program and HR-coupled repair.…”
Section: Long-term Atr Inhibition Bypasses Overexpression Of E2f1mentioning
confidence: 69%
“…Importantly, our ability to overcome induced E2F1 overexpression by long-term ATR inhibition indicates that resection and HR capacity can be remodeled independently of the levels of E2F transcription. This finding should be relevant to addressing ATRi-mediated therapies in tumors that are highly dependent on E2F transcription or in tumors that have built an adaptive response to chemotherapy 71,72 .…”
Section: Long-term Atr Inhibition Bypasses Overexpression Of E2f1mentioning
confidence: 90%
“…Given its roles in DNA damage tolerance, now including the traverse of ICLs, it could be predicted that PrimPol protects cells from the toxicity of DNA crosslinking agents. In this regard, PRIMPOL KO cells displayed hypersensitivity to cisplatin (Quinet et al, 2020) and MMC (Figure 5A). To test the relevance of this protective function in vivo, WT and PRIMPOL KO mice were treated with different concentrations of MMC.…”
Section: Hypersensitivity Of Primpol Ko Mice To MMCmentioning
confidence: 98%
“…Following UV-C irradiation or treatment with cisplatin, PrimPol accumulates on chromatin to facilitate the replicative bypass of DNA photoadducts or cisplatin-induced lesions Quinet et al, 2020). To test whether PrimPol is recruited to chromatin in response to ICLs, we analyzed its subcellular localization in response to MMC (that induces DNA monoadducts, intra-strand crosslinks and ICLs), or trimethylpsoralen activated with UVA (TMP-UVA), which induces ICLs with high specificity (~90% of total lesions; Lopez-Martinez et al, 2016).…”
Section: Primpol Facilitates Dna Synthesis In Response To Icl-inducinmentioning
confidence: 99%
See 1 more Smart Citation